Do audit firm reputation provide insight into financial reporting quality? Evidence from accrual and real management of listed companies in Vietnam - Ngoc Mai Tran; Manh Ha Tran (Cogent Business & Management, 2023)
The purpose of this paper is to investigate whether audit firm reputation provides insight into financial reporting quality of listed companies in Vietnam. Earning management measured by accrual earning management and real earning management is compared between firms audited by Big 4 auditors and non-Big 4. Using difference in differences approach on the sample of 331 listed companies in Vietnam during 2013-2020, the study finds that Big 4 improves financial report quality through decreasing earning management. The role of Big 4 auditor in monitoring real earing management is more significant than accrual earning management in auditing year because real earning management has been preferred over accrual in years before. This study could provide valuable information for investors and shareholders when using financial report as well as the Government administration in preventing earning management practices and promoting high level of accounting and auditing compliance.
Keywords: 650; earning management; Big 4; real earning management